Christian values and their relationship with management variables in Ecuador: Application of christian values in the production and hiring process - Armas Herrera, Reinaldo; Ugando Peñate, Mikel; Higuerey Gómez, Ángel Alexander; Sabando García, Ángel Ramón; Pilay Toala, Félix Sixto (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Christian Values are now more relevant because companies are not only concerned with profit. Through a sample of 176 companies in zone 4 of Ecuador, the application of the values of solidarity, honesty, humility and responsibility in the production and hiring processes has been studied. The objective is to find out if these values are relevant in management. As a result, it was found that there are few companies that take into account these declared values as such. The absence of these values indicates that companies must incorporate them to have greater sustainability and social responsibility.